The impact of social media in spreading Da'wah and Islamic knowledge: Bangladesh perspective - Jannat, Shadeka (IIUC Studies, 2026)
Social media has become an essential component of modern communication, allowing people and organizations to immediately contact a large audience. In Bangladesh, where Islam is the most practiced religion, social media platforms have grown to be effective resources for promoting Da'wah (inviting people to Islam) and distributing Islamic information. This study explores the positive and negative effects of social media on spreading Da'wah and Islamic knowledge in Bangladesh. A qualitative approach has been followed to conduct this study. Data have been collected through document analysis. According to the findings, the positive impacts of social media in spreading Da’wah and Islamic knowledge are: spreading the Holy Quran, Sunnah, and many Islamic apps, showing the true face of Islam, the ease of spreading Da’wah, sharing authentic knowledge, etc., and the negative impacts are: false news is generated and spread through social media, lack of authenticity and verification, misinformation and misinterpretation, spread of extremist views etc. This study will be helpful for young generation to use the social media for the purpose of goodness so that they can attain success in here and hereafter. IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 149-168